The Effect Of Tax Rates, Penalties, Taxpayer Awareness, and Tax Knowledge On MSME Taxpayer Compliance - Zhafira, Khairunnisa Alvania; Agustina, Heni (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to examine the effect of tax rates, penalties, taxpayer awareness, and tax knowledge on the tax compliance of MSMEs. This study uses a population of MSMEs registered in Sidoarjo Regency with a sample of 90 MSMEs. This study uses SPSS 30.0 software. The results of this study indicate that tax rates and penalties do not affect the tax compliance of MSMEs, while taxpayer awareness and tax knowledge do affect the tax compliance of MSMEs